IMPLICIT SENSER AND PHENOMENON IN MENTAL PROCESS FOUND IN HORSE GIRL MOVIE - Nurjannah; Sahur Saerudin (J-Shelves of Indragiri (JSI), 2024)
Investigating mental process is highly significant because it provides a framework for understanding how language represents human experiences involving the cognitive and emotional activities of the mind. The research aims to describe the implicit senser and phenomenon as a clause structure in mental process found in the main character in the Horse Girl movie. The researchers used descriptive qualitative as the research method. The data are taken from the utterances of the main character in the movie. The data collection techniques are carried out by downloading, watching, reading, identifying, classifying data and encoding data containing mental process. The data analysis techniques are carried out by presenting, describing, interpreting, and concluding the results of this researcher based on Halliday's theory of Systemic Functional Linguistics. The researchers found that the data showed language choices in mental process reflecting the speaker's perspective and subjectivity which encoded the main character’s perception and cognition. Based on the result of the research, the senser and the phenomenon are expressed implicitly which convey the main character's emotional or psychological state without explicitly stating it through dialogue.